2019
DOI: 10.1111/jfpe.13000
|View full text |Cite|
|
Sign up to set email alerts
|

Development and validation of mathematical modeling for terminal velocity of cantaloupe

Abstract: Terminal velocity is an important factor, which is useful for designing different unit operations such as hydro transport and sorting of fruits. The current investigation is aimed to propose a new dimensionless model for terminal velocity of cantaloupe fruit. For this purpose, 30 fruits from three different varieties commonly known as Jana, Gerdabadi, and Shahabadi randomly were collected and, then, the physical properties, which may affect terminal velocity, were determined. On the basis of Buckingham theorem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Also, the data obtained about the hydrodynamic properties of cantaloupe can be used in the transfer, separation, and sorting through water in order to reduce processing costs and product waste. In similar studies, researchers reported that parameters such as the buoyance force and drag force can be used in modeling terminal velocity and the time length for the fruit to move up or down in the fluid (Dadashi et al, ; Jahanbakhshi et al, ; Moradi et al, ; Tarighi, Mohtasebi, Heydari, & Abasghazvini, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the data obtained about the hydrodynamic properties of cantaloupe can be used in the transfer, separation, and sorting through water in order to reduce processing costs and product waste. In similar studies, researchers reported that parameters such as the buoyance force and drag force can be used in modeling terminal velocity and the time length for the fruit to move up or down in the fluid (Dadashi et al, ; Jahanbakhshi et al, ; Moradi et al, ; Tarighi, Mohtasebi, Heydari, & Abasghazvini, ).…”
Section: Resultsmentioning
confidence: 99%
“…Then, to determine the dimensions and mass of the samples under experiment, a digital caliper with the precision of 0.01 mm, and a digital scale with the accuracy of 0.01 g, were used. Geometric mean diameter ( D g ), arithmetic mean diameter ( D a ) and sphericity percentage ( φ ) were calculated through relations (1)–(3) (Moradi et al, ). Dg=italicLWT1/3 Da=L+W+T3 φ=DnormalgL where L , W , and T were the length, width, and thickness of the cantaloupes, respectively. The surface area ( S ) of the samples was calculated using relation (4) in which π equals 3.14 (Shahbazi & Rahmati, ). S=πDg2 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…About 30 samples of whole tubers were randomly selected whose dimensions were measured with via Vernier caliper with an accuracy of 0.01 mm. Also, the sphericity, arithmetic, and geometric mean diameter and surface area of the samples were calculated (Moradi, Mousavi Khaneghah, Parvaresh, & Balanian, ). Table presents some characteristics of the tested potato.…”
Section: Methodsmentioning
confidence: 99%
“…According to the FAO report, about 78,000 ha of Iranian agricultural lands have been occupied by cucumber and gherkin cultivations (FAO, ). Since a large amount of harvested cucumber was used for the production of pickles, recognizing the physical and hydrodynamic properties of cucumber seems to be crucial in sketch, adjustment, and development of washing and grading machines (Moradi, Mousavi Khaneghah, Parvaresh, & Balanian, ). Furthermore, the determination of physical dimensions, volume, mass, and density of cucumber are among the most interesting points in the post‐harvesting machinery of this crop (Rao, Rizvi, Datta, & Ahmed, ).…”
Section: Introductionmentioning
confidence: 99%